Optimizing garbage collection vehicle routing problem with alternative fuel-powered vehicles. (2nd November 2017) - Gajpal, Yuvraj; Abdulkader, M. M. S.; Zhang, Shuai; Appadoo, S. S.
Abstract: This paper considers the garbage collection problem in which vehicles with multiple compartments are used to collect the garbage. The vehicles are considered to be Alternative Fuel-powered Vehicles (AFVs). Compared with the traditional fossil fuel powered vehicles, the AFVs have limited fuel tank capacity. In addition, AFVs are allowed to refuel only at the depot. We provide a mathematical formulation and develop two solution approaches to solve the problem. The first approach is based on the saving algorithm, while the second is based on the ant colony system (ACS) metaheuristic. New problem instances have been generated to evaluate the performance of the proposed algorithms.